2007
DOI: 10.1093/nar/gkm750
|View full text |Cite
|
Sign up to set email alerts
|

Deaminase-independent inhibition of HIV-1 reverse transcription by APOBEC3G

Abstract: APOBEC3G (A3G), a host protein that inhibits HIV-1 reverse transcription and replication in the absence of Vif, displays cytidine deaminase and single-stranded (ss) nucleic acid binding activities. HIV-1 nucleocapsid protein (NC) also binds nucleic acids and has a unique property, nucleic acid chaperone activity, which is crucial for efficient reverse transcription. Here we report the interplay between A3G, NC and reverse transcriptase (RT) and the effect of highly purified A3G on individual reactions that occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
278
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(293 citation statements)
references
References 73 publications
15
278
0
Order By: Relevance
“…Moreover, the addition of the first deoxynucleotide to the 3 0 -hydroxyl of the tRNA Lys primer is not discernibly inhibited, implying that tRNA Lys placement at the PBS of the viral RNA is unaffected by A3G. These findings, together with results obtained using reconstituted in vitro systems (Iwatani et al 2007), indicate that A3G does not directly inhibit the biosynthetic capabilities of the reverse transcriptase enzyme but, rather, impedes its progression along template RNA (figure 3). The molecular mechanism for this effect continues to be investigated, but A3G's capacity to bind single-stranded RNA and thereby sterically hinder the translocation of reverse transcriptase would lead to the observed polarity of inhibition to cDNA accumulation.…”
Section: Cytidine Deamination Independent Effects Of Apobec3g On Hiv-1mentioning
confidence: 77%
“…Moreover, the addition of the first deoxynucleotide to the 3 0 -hydroxyl of the tRNA Lys primer is not discernibly inhibited, implying that tRNA Lys placement at the PBS of the viral RNA is unaffected by A3G. These findings, together with results obtained using reconstituted in vitro systems (Iwatani et al 2007), indicate that A3G does not directly inhibit the biosynthetic capabilities of the reverse transcriptase enzyme but, rather, impedes its progression along template RNA (figure 3). The molecular mechanism for this effect continues to be investigated, but A3G's capacity to bind single-stranded RNA and thereby sterically hinder the translocation of reverse transcriptase would lead to the observed polarity of inhibition to cDNA accumulation.…”
Section: Cytidine Deamination Independent Effects Of Apobec3g On Hiv-1mentioning
confidence: 77%
“…Because of the difficulties in detecting eqA3-derived cytidine deamination in EIAV genomes, we studied the relevance of the zinc coordination domain for the antiviral activity. It has been reported that cytidine deamination is largely dispensable for the inhibition HIV-1 ⌬vif by human A3F and A3G (4,30,46,61). But controversially, several groups have reported a significant drop in inhibition observed when active-site mutants of human A3G were analyzed (8,9,22,23,56,75).…”
Section: Vol 83 2009 Restriction Of Eiav By Apobec3 7551mentioning
confidence: 99%
“…Incorporated A3G specifically deaminates cytosine residues to uracil in growing singlestranded DNA during reverse transcription, leading to HIV genome degradation or hypermutation (5,25,39,48,49,98). More recent studies indicate that deaminase-independent mechanisms might also be involved in antiviral activity of A3 (4,27,28,30,54,61). The amount of encapsidated A3G in wild-type (wt) HIV-1 virions is dramatically reduced by a Vifdependent degradation via the ubiquitination-proteasome pathway (50,79,94,95).…”
mentioning
confidence: 99%
“…As a result, numerous guanosine (G) to adenosine (A) changes in the plus strand of the provirus occur [also referred to as ''hypermutated'' proviruses (3,12,13)]. In addition, APO-BEC3 may exert antiviral activity in the target cell in an editing-independent manner, by interfering with tRNA primer binding (14), provirus formation, and/or viral cDNA integration (15)(16)(17).…”
mentioning
confidence: 99%